Electrophoretic and electrochromatographic separation of proteins in capillaries: An update covering 2007-2009 - El Rassi, Ziad (Electrophoresis, 2010)
This review article covers 3-year period from 2007 to 2009 and is a continuation of the review article by V. Dolnik, [Electrophoresis 2008, 29, 143-156]. This article with 125 references describes recent developments in CE and CEC of proteins in capillary format and does not cover the developments of CE and CEC in microchip format, since Tran et al. review the microchip subject in this special issue. The present review article has four major topics including (i) the separation media, (ii) multidimensional separations, (iii) detection, and (iv) applications.